Evaluation of dietary supplementation of Ascophyllum nodosum and Lithothamnium calcareum as functional algae in F4+ Escherichia coli challenged piglets - Dell’Anno, Matteo; Frazzini, Sara; Reggi, Serena; Ferri, Irene; Scaglia, Elena; Schiasselloni, Linda; Inglesi, Alessia; Riva, Federica; Verdile, Nicole; Pasquariello, Rolando; Rossi, Luciana (Frontiers in Veterinary Science, 2024)
IntroductionDespite progress in reducing antimicrobial use in the veterinary field, it is crucial to find alternatives to preserve effectiveness and limit antimicrobial resistance. In pig farming, pathogenic strains of E. coli are the main cause of gastrointestinal disorders and antibiotic use. In this field, algae represent an innovation in animal nutrition that aligns with livestock sustainability principles and provide a high content of functional molecules.AimThe aim of this study was to evaluate the impact of an innovative dietary combination of Ascophyllum nodosum and Lithothamnium calcareum, on growth, duodenum gene expression, jejunum intestinal morphology, and serum oxidative status in F4+ Escherichia coli challenged piglets.Materials and methodsForty-eight weaned pigs, aged 28 ± 2 days, were divided into two groups (n = 24 pigs/group): the control group was fed a commercial diet (CTRL), while the seaweeds group was fed a commercial diet supplemented with 1.5% A. nodosum and 0.5% L. calcareum for 27 days (ALGAE). After 13 days, 50% of animals in each group were challenged with a single dose of 108 CFU/dose of E. coli F4+, resulting in two infected groups (CTRL+ and ALGAE+, n = 12 pigs/group). Growth performance was assessed by measuring the individual body weight. At day 27, from six animals/group duodenum and jejunum sections were sampled for gene expression analysis via qRT-PCR and histological evaluation.Results and discussionThe results indicated a significantly higher body weight in the ALGAE+ group compared to CTRL+ after 7 days post-challenge (p < 0.0001). Jejunum morphology revealed lower villus height, villus width and villus height/crypt depth ratio in CTRL+ compared to ALGAE+ (p < 0.05) suggesting a protective effect of seaweeds on gut health.ConclusionIn conclusion, algae mixture exerted a protective effect against intestinal damage from E. coli F4+ infection proposing A. nodosum and L. calcareum supplementation as interesting strategy to support animal growth, enhance health and reduce antibiotic treatments in weaned piglets.